2018
DOI: 10.1089/bfm.2018.0020
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Factors That Impact Breastfeeding Duration in the Postpartum Period: A Secondary Analysis of PRAMS Data

Abstract: These results underscore the importance of hospitals adopting evidence-based best practices for breastfeeding. The relationship found between Women, Infants, and Children receiving supplemental nutrition benefits and breastfeeding quit times requires further exploration. The study results also highlight the need to address modifiable factors that may be overlooked in traditional breastfeeding promotion efforts, such as depression and alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…[11][12][13][14] More recent research has begun to tease apart the modifying effects of age, race, psychosocial and lifestyle factors, and offspring health status on the relationship between hospital practices and breastfeeding duration. 6,[14][15][16][17][18][19] Further research, particularly among population-based samples that include at-risk women, regarding how hospital practices influence breastfeeding success is needed. Such research is particularly needed within states that fall behind BFHI designation, including Utah that makes up only one of the 539 (0.002%) BFHI designated facilities in the United States despite having the highest birthrate in the country (Utah: 16.9 births/1,000 women; United States: 12.4 births/1,000 women).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] More recent research has begun to tease apart the modifying effects of age, race, psychosocial and lifestyle factors, and offspring health status on the relationship between hospital practices and breastfeeding duration. 6,[14][15][16][17][18][19] Further research, particularly among population-based samples that include at-risk women, regarding how hospital practices influence breastfeeding success is needed. Such research is particularly needed within states that fall behind BFHI designation, including Utah that makes up only one of the 539 (0.002%) BFHI designated facilities in the United States despite having the highest birthrate in the country (Utah: 16.9 births/1,000 women; United States: 12.4 births/1,000 women).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this limitation, cross-sectional data have revealed that breastfeeding in the first hour after birth, avoiding supplementation, rooming-in, avoiding pacifier use, breastfeeding on demand, and postdischarge breastfeeding support are all supportive of short-term breastfeeding duration. [10][11][12][13][14] A dose-response relationship between the Ten Steps and breastfeeding duration is supported in the literature. DiGirolamo and colleagues found that only 3% of women exposed to at least six steps quit breastfeeding before 6 weeks postpartum, whereas 30% of those who had not received any of the Ten Steps quit during this period.…”
Section: Introductionmentioning
confidence: 84%
“…Avoiding inpatient formula supplementation for nonmedical reasons has been associated with longer exclusive and partial breastfeeding duration in the literature. [11][12][13][14][25][26][27] However, others found no effect of formula supplementation on breastfeeding outcomes. [28][29][30] It is hypothesized that formula supplementation may interfere with the physiology of milk production because of an interruption of the natural balance between supply and demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,8,9 Most data regarding breastfeeding rates in premature infants are limited to observational studies with small cohorts or short-term follow-up. [10][11][12] The limited success of interventions to improve breastfeeding outcomes in premature infants raises the question of whether low rates of breastfeeding initiation and continuation in this group are specifically related to prematurity, or are confounded by socio-economic or cultural characteristics that are challenging to address in the context of a clinic-or hospital-based intervention. The available evidence on the association between prematurity and breastfeeding outcomes is not well equipped to resolve this question, as it relies primarily on cross-sectional data, such as the Pregnancy Risk Assessment Monitoring System, the Infant Feeding Practices Study, and single-centre studies focusing on a particular hospital or neonatal intensive care unit.…”
Section: Introductionmentioning
confidence: 99%